Vulnerabilidade e áreas prioritárias para coleta de Phyllocycla (Calvert, 1948) no Brasil - Araújo, Maysa Farias de Almeida (2016)
The loss and habitat fragmentation are among the main threats to biodiversity in the world. Given this and the need to promote studies with rare or endangered species, in order to generate knowledge and mitigate possible impacts, we use modeling techniques to identify priority areas for collection and to evaluate the vulnerability of a genus of Odonata occurring mainly in Brazil, Phyllocycla. We selected priority areas for collecting by associating a climatic suitability map, resulting from the distribution modeling, with a distance map, which considers the distance between each cell of the interest area and the nearest occurrence point. Thus, the areas considered as priority for collection were those with high climatic suitability and greater distance from known collection points. For the vulnerability analysis, we related the distribution models with the area occupied by the existing anthropic activities and those planned by the Brazilian government. We identified that the priority areas for collecting Phyllocycla in Brazil comprises mainly the southern Amazon region and some fragments of Cerrado in the northeast and center-west regions. The geographical distribution of Phyllocycla is possibly underestimated in Brazil, since the records are distributed unevenly throughout the country, with only a few well-sampled regions, such as southeastern Brazil and northern Amazon region. We found that only 55.3% of the original potential distribution of Phyllocycla in Brazil remains available. The area compromised by anthropic activities comprises mainly the Cerrado and Atlantic Forest biomes, with less impact in the Amazon. However, with the implementation of activities already planned by the Brazilian government, it is possible that an additional 13.6% of this area will be unavailable to species of Phyllocycla, especially in the Amazon, where interest in mining and the implementation of new hydroelectric production has increased. We recomend the use of our models to support possible action plans for endangered Phyllocycla species and that vulnerability models will help public managers in decision making, especially in the licensing of new activities.